Evaluation of Some Fungicides in Controlling Blast of Rice var. Kalijira in Mymensingh - Sultana, Rajia; Fatema-Tuz-Zohura; Rahman, Md. Atikur; Hasan, Ahmed Khairul; Miah, M Bahadur; Hossain, Muhammed Ali (Journal of the Bangladesh Agricultural University, 2024)
Bioassay of sixteen chemical fungicide(s) was done against Pyricularia oryzae in in vitro following poisoned food technique in the Plant Microbe Interaction Lab (PMIL), Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh-2202. Total inhibition (100%) of mycelial growth of Pyricularia oryzae was obtained by Tebuconazol 50% + Trifloxistrobin 25% (Nativo 75WG), Trifloxistrobin 25% + Tebuconazol 50% (Blastin), Carbendazim 50% (Autostin 50 WDG), Tebuconazol 25% (Folicur EW 250), Hexaconazol 50% (Contaf 5EC), Mancozeb 80% (Indofil M 45), Zineb 68% + Hexaconazole l4% (Awal 72 WP) and Propiconazol (Proven) containing fungicides at the lowest (0.0125%) concentration. Based on in vitro performance and their availability to the farmers, five fungicides (Nativo 75WG, Autostin 50 WDG, Folicur EW 250, Contaf 5EC and Companion) were selected and sprayed in the field onto the foliage of rice plants in two different concentrations (0.1% and 0.2%) to evaluate the efficacy in reducing rice blast incidence and severity and increasing some yield contributing parameters. Among the fungicides used, two times spray (at 45 DAT and 52 DAT) of Nativo 75 WG @ 0.2% concentration showed the best performance in reducing blast incidence (4.31% and 0.00% for leaf and neck blast respectively) and severity (12.4% and 12.6% at 52 and 59 DAT respectively) as well as increasing the yield parameters followed by Autostin 50 WDG @ 0.2% concentration. It is therefore summarized that two times application of Nativo 75 WG or Autostin 50 WDG @ 2g/L of water starting from the late tillering stage will be effective for the control blast disease in field conditions. J Bangladesh Agril Univ 18(4): 941–948, 2020 https://doi.org/10.5455/JBAU.136288